The Meaning of Flexing Luxury Brand in Social Media Based on the Perception of Generation Z - Cindy Wijaya; Intan Primadini (LONTAR: Jurnal Ilmu Komunikasi, 2023)
The trend of utilizing luxury brands among Generation Z in Indonesia is on the rise. The shifting landscape of priorities among young individuals in this evolving era often results in tertiary needs taking precedence as primary necessities. Consequently, a hedonistic mindset emerges when indulging in luxury brand consumption. Furthermore, the inclination towards specific luxury brands goes beyond mere consumption; it fosters the development of a brand-focused lifestyle among the youth. Hence, a research initiative was undertaken to elucidate how Generation Z perceives luxury brands. Employing an interpretative phenomenological analysis (IPA) within a constructivist framework, alongside a qualitative exploratory approach, the study aimed to uncover participants' interpretations of luxury brands. Data were acquired through interviews, subsequently subjected to analysis using methodologies outlined by Smith, Flowers, and Larkin. The research findings underscored that one of the catalysts for this phenomenon lies in Generation Z's aspiration for acknowledgment and acceptance within society. Financial, functional, social, and individual values collectively contribute to shaping the significance attached to luxury brands among this demographic. Generation Z holds the belief that social validation can be garnered by enhancing their standard of living or social status through the adoption of luxury brands, fostering hedonism and brand-conscious behavior.